Examining Traditional Winter Preparations: The Case of Bitlis Cuisine - ŞİMŞEK, Aykut; ÇELİK YEŞİL, Seher (Bitlis Eren University, 2022)
Today, the term that corresponds to winter preparation is to ensure that the products produced in the season take place in human nutrition for a longer period of time due to their biological and physical structures. It is also a method of preservation. Considering the 81 provinces of Turkey's geography, it is thought that each region has its own winter preparations. This study aims to examine the winter preparations of Bitlis cuisine. In this direction, interviews were conducted with 13 female participants between 20-25 December 2021 using the semi-structured interview technique. As a result of the interviews, it was determined that the winter preparations were for drying, fermentation, and meat products. Among them, it has been determined that there are products such as sauerkraut called çörti, salted cabbage brine called şör leaf, dried meat, dried head and leg and dried fish, basma cheese, which is kept in the soil and kept for five or six months to mellow. In addition, fruits and vegetables obtained from the temperate districts of the region are dried and stored.
Keywords: Bitlis cuisine; winter preparations; traditional.; Bitlis mutfağı; kış hazırlıkları; geleneksel.; 2. Zero hunger